Download presentation
1
3.6 Systems with Three Variables
Solving Three-Variable Systems by Substitution
2
2) Solving Three-Variable Systems by Substitution
Substitution may be easier in cases where an equation can be solved for one variable Example: x + 32y – 32.7z = -382 Rewrite as: x = -382 – 32y z
3
2) Solving Three-Variable Systems by Substitution
Example 1: Solve the system by substitution x – 2y + z = -4 -4x + y – 2z = 1 2x + 2y – z = 10 {
4
2) Solving Three-Variable Systems by Substitution
Example 1: Solve the system by substitution x – 2y + z = -4 -4x + y – 2z = 1 2x + 2y – z = 10 Re-write (1) as x =. { 1 2 3
5
2) Solving Three-Variable Systems by Substitution
Example 1: Solve the system by substitution x – 2y + z = -4 -4x + y – 2z = 1 2x + 2y – z = 10 Re-write (1) as x =. x = y – z { 1 2 3 1
6
2) Solving Three-Variable Systems by Substitution
Example 1: Solve the system by substitution x – 2y + z = -4 -4x + y – 2z = 1 2x + 2y – z = 10 Now…it gets ugly. Sub x = y – z in { 1 2 3 2
7
2) Solving Three-Variable Systems by Substitution
Example 1: Solve the system by substitution x – 2y + z = -4 -4x + y – 2z = 1 2x + 2y – z = 10 Sub x = y – z in { 1 2 3 2 2
8
2) Solving Three-Variable Systems by Substitution
Example 1: Solve the system by substitution x – 2y + z = -4 -4x + y – 2z = 1 2x + 2y – z = 10 Sub x = y – z in -4(-4 + 2y – z) + y – 2z = 1 { 1 2 3 2 2
9
2) Solving Three-Variable Systems by Substitution
Example 1: Solve the system by substitution x – 2y + z = -4 -4x + y – 2z = 1 2x + 2y – z = 10 Sub x = y – z in -4(-4 + 2y – z) + y – 2z = 1 16 – 8y + 4z + y – 2z = 1 -7y + 2z = -15 { 1 2 3 2 2 4
10
2) Solving Three-Variable Systems by Substitution
Example 1: Solve the system by substitution x – 2y + z = -4 -4x + y – 2z = 1 2x + 2y – z = 10 Sub x = y – z in { 1 2 3 3 3
11
2) Solving Three-Variable Systems by Substitution
Example 1: Solve the system by substitution x – 2y + z = -4 -4x + y – 2z = 1 2x + 2y – z = 10 Sub x = y – z 2(-4 + 2y – z) + 2y – z = 10 { 1 2 3 3 3
12
2) Solving Three-Variable Systems by Substitution
Example 1: Solve the system by substitution x – 2y + z = -4 -4x + y – 2z = 1 2x + 2y – z = 10 Sub x = y – z 2(-4 + 2y – z) + 2y – z = 10 -8 + 4y – 2z + 2y – z = 10 6y – 3z = 18 { 1 2 3 3 3 5
13
2) Solving Three-Variable Systems by Substitution
Example 1: Solve the system by substitution x – 2y + z = -4 -4x + y – 2z = 1 2x + 2y – z = 10 Solve for y and z with elimination, substitution. -7y + 2z = -15 6y – 3z = 18 { 1 2 3 4 5
14
2) Solving Three-Variable Systems by Substitution
Example 1: Solve the system by substitution x – 2y + z = -4 -4x + y – 2z = 1 2x + 2y – z = 10 Solve for y and z with elimination, substitution. -7y + 2z = -15 x 3 6y – 3z = 18 x 2 { 1 2 3 4 5
15
2) Solving Three-Variable Systems by Substitution
Example 1: Solve the system by substitution x – 2y + z = -4 -4x + y – 2z = 1 2x + 2y – z = 10 Solve for y and z with elimination, substitution. -7y + 2z = -15 x y + 6z = -45 6y – 3z = 18 x y – 6z = 36 { 1 2 3 4 5
16
2) Solving Three-Variable Systems by Substitution
Example 1: Solve the system by substitution x – 2y + z = -4 -4x + y – 2z = 1 2x + 2y – z = 10 Solve for y and z with elimination, substitution. -7y + 2z = -15 x y + 6z = -45 6y – 3z = 18 x y – 6z = 36 -9y = -9 y = 1 { 1 2 3 4 5
17
2) Solving Three-Variable Systems by Substitution
Example 1: Solve the system by substitution x – 2y + z = -4 -4x + y – 2z = 1 2x + 2y – z = 10 Solve for y and z with elimination, substitution. -7y + 2z = -15 -7(1) + 2z = -15 2z = z = -4 { 1 2 3 4 4 Sub y = 1 in
18
2) Solving Three-Variable Systems by Substitution
Example 1: Solve the system by substitution x – 2y + z = -4 -4x + y – 2z = 1 2x + 2y – z = 10 Solve for x. x = y – z x = (1) –(-4) x = x = 2 { 1 2 3 Sub y = 1, z = -4.
19
2) Solving Three-Variable Systems by Substitution
Example 1: Solve the system by substitution x – 2y + z = -4 -4x + y – 2z = 1 2x + 2y – z = 10 Therefore, the solution is (2, 1, -4). { 1 2 3
20
2) Solving Three-Variable Systems by Substitution
Example 2: Solve the system by substitution x + 7y + 5z = 16 -2x + y – 14z = -9 -3x - 2y + 9z = -12 {
21
2) Solving Three-Variable Systems by Substitution
Example 2: Solve the system by substitution x + 7y + 5z = 16 -2x + y – 14z = -9 -3x - 2y + 9z = -12 Rearrange Sub in and { 1 2 3 2 1 3
22
2) Solving Three-Variable Systems by Substitution
Example 2: Solve the system by substitution x + 7y + 5z = 16 -2x + y – 14z = -9 -3x - 2y + 9z = -12 Rearrange Sub in and y = x + 14z { 1 2 3 2 1 3 2
23
2) Solving Three-Variable Systems by Substitution
Example 2: Solve the system by substitution x + 7y + 5z = 16 -2x + y – 14z = -9 -3x - 2y + 9z = -12 Rearrange Sub in and y = x + 14z x + 7y + 5z = 16 { 1 2 3 2 1 3 2 1
24
2) Solving Three-Variable Systems by Substitution
Example 2: Solve the system by substitution x + 7y + 5z = 16 -2x + y – 14z = -9 -3x - 2y + 9z = -12 Rearrange Sub in and y = x + 14z x + 7y + 5z = 16 12x + 7(-9 + 2x + 14z) + 5z = 16 12x x + 98z + 5z = 16 26x + 103z = 79 { 1 2 3 2 1 3 2 1 4
25
2) Solving Three-Variable Systems by Substitution
Example 2: Solve the system by substitution x + 7y + 5z = 16 -2x + y – 14z = -9 -3x - 2y + 9z = -12 Rearrange Sub in and y = x + 14z x - 2y + 9z = -12 -3x - 2(-9 + 2x + 14z) + 9z = -12 { 1 2 3 2 1 3 2 3
26
2) Solving Three-Variable Systems by Substitution
Example 2: Solve the system by substitution x + 7y + 5z = 16 -2x + y – 14z = -9 -3x - 2y + 9z = -12 Rearrange Sub in and y = x + 14z x - 2y + 9z = -12 -3x - 2(-9 + 2x + 14z) + 9z = -12 -3x + 18 – 4x – 28z + 9z = -12 -7x - 19z = -30 { 1 2 3 2 1 3 2 3 5
27
2) Solving Three-Variable Systems by Substitution
Example 2: Solve the system by substitution x + 7y + 5z = 16 -2x + y – 14z = -9 -3x - 2y + 9z = -12 Add and 26x + 103z = 79 -7x - 19z = -30 { 1 2 3 4 5 4 5
28
2) Solving Three-Variable Systems by Substitution
Example 2: Solve the system by substitution x + 7y + 5z = 16 -2x + y – 14z = -9 -3x - 2y + 9z = -12 Add and 26x + 103z = 79 x x + 721z = 553 -7x - 19z = -30 x x – 494z = -780 { 1 2 3 4 5 4 5
29
2) Solving Three-Variable Systems by Substitution
Example 2: Solve the system by substitution x + 7y + 5z = 16 -2x + y – 14z = -9 -3x - 2y + 9z = -12 Add and 26x + 103z = 79 x x + 721z = 553 -7x - 19z = -30 x x – 494z = -780 227z = -227 z = -1 { 1 2 3 4 5 4 5
30
2) Solving Three-Variable Systems by Substitution
Example 2: Solve the system by substitution x + 7y + 5z = 16 -2x + y – 14z = -9 -3x - 2y + 9z = -12 Sub z = -1 in 26x + 103z = 79 26x + 103(-1) = 79 x = 7 { 1 2 3 4
31
2) Solving Three-Variable Systems by Substitution
Example 2: Solve the system by substitution x + 7y + 5z = 16 -2x + y – 14z = -9 -3x - 2y + 9z = -12 Sub z = -1 and x = 7 in 12x + 7y + 5z = 16 12(7) + 7y + 5(-1) = 16 84 + 7y – 5 = 16 y = -9 { 1 2 3 1
32
2) Solving Three-Variable Systems by Substitution
Example 2: Solve the system by substitution x + 7y + 5z = 16 -2x + y – 14z = -9 -3x - 2y + 9z = -12 Therefore, the solution is (7, -9, -1). { 1 2 3
33
Homework p.157 #10-12, 28, 29, 38, 39 ASSIGNMENT: 3.5, 3.6 on Monday Oct 19 QUIZ: 3.5, 3.6 on Wednesday Oct 21 TEST: 3.1, 3.2, 3.5, 3.6 on Monday Oct 26 Halloween Party: Friday October 30 5-8pm Dancing, food and games
Similar presentations
© 2025 SlidePlayer.com. Inc.
All rights reserved.